Teachers' and students' perception and attitudes to the application of New Dynamic English at Hanoi University of Business and Technology - Mai, Thi Nga (ĐHNN, 2017)
Today the application of information technology and software in teaching are a prevailing trend in the world, especially in the field of teaching foreign languages. Dyned software is being selected by some of the countries to teach English as a foreign lan (...)